2020
DOI: 10.1093/jpp/rgaa042
|View full text |Cite
|
Sign up to set email alerts
|

Paeoniflorin modulates oxidative stress, inflammation and hepatic stellate cells activation to alleviate CCl4-induced hepatic fibrosis by upregulation of heme oxygenase-1 in mice

Abstract: Objectives The role of Paeoniflorin on hepatic fibrosis and the specific mechanisms has not yet been elucidated. Therefore, we explored whether Paeoniflorin exerted protective effects on carbon tetrachloride (CCl4)-induced hepatic fibrosis and the underlying mechanisms. Methods A model of hepatic fibrosis was induced by intraperitoneally injecting with CCl4 (10% 5 μl/g) twice a week for 7 weeks. To explore the effects of Paeo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…This model exhibits a strong inflammatory response and high levels of apoptosis. [52][53][54][55] This is consistent with the results of the present study. It is important to emphasize that SS and ST at equimolar doses administered with silibinin more significantly reduced the expression of proinflammatory factors in the liver and also better regulated the expression of apoptosis-related proteins.…”
Section: Discussionsupporting
confidence: 93%
“…This model exhibits a strong inflammatory response and high levels of apoptosis. [52][53][54][55] This is consistent with the results of the present study. It is important to emphasize that SS and ST at equimolar doses administered with silibinin more significantly reduced the expression of proinflammatory factors in the liver and also better regulated the expression of apoptosis-related proteins.…”
Section: Discussionsupporting
confidence: 93%
“…PF is a novel HSP-inducing compound that enhances the expression of Heat Shock Proteins (HSPs). In addition, it exhibits protective effects against various stressors [39]. Numerous studies have highlighted the potential bene ts of PF, including ROS generation reduction [29,40] and maintenance of a balanced Excessive ROS accumulation is a key contributor to apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Stress in Hepatocytes. Previous studies have reported that CCL4 induces the accumulation of free radicals in hepatocytes, leading to oxidative stress injury [18]. Thus, to further study the biological basis of the protective effect of HBO1 on hepatocytes, we analyzed the effect of HBO1 on CCL4induced hepatic oxidative damage.…”
Section: Hbo1 Knockdown Alleviated Ccl4-induced Oxidativementioning
confidence: 99%